Artificial Intelligence (AI) and the Development of the Legal Profession - Grace Juanita; Budi Prastowo (Law Development Journal, 2026)
Amidst rapid technological advancement, this study investigates the influence of Artificial Intelligence (AI) on human relationships and the safeguarding of human dignity. The research questions whether AI’s current trajectory aligns with ethical standards and preserves the core values of human interaction. This study aims to analyze the impact of Artificial Intelligence (AI) development and utilization on changing patterns of human relationships and to assess its implications for the protection of human dignity. Using a normative juridical approach combined with interdisciplinary analysis from ethics and philosophy, the study critically assesses both the advantages, and the ethical risks associated with AI integration. It explores how AI reshapes traditional social dynamics and tests existing legal-ethical frameworks. Through a review of selected case studies and theoretical discourse, the paper identifies deficiencies in existing regulations and emphasizes the urgent need for comprehensive ethical and legal standards. The findings highlight the importance of redefining ethical practices within legal frameworks to ensure justice, transparency, and the continuous protection of human dignity amid evolving AI technologies. The study concludes that AI should function as a supportive tool for legal professionals rather than a substitute for human judgment, with its development and utilization.